Disseminated Histoplasmosis as an AIDS-Defining Illness Presenting as Fever of Unknown Origin in an 11-Year-Old Female - Kathryn E. Kalata; Christina Osborne; Amy Willis; Kacey Navarro; Laura Z. Fenton; Christiana Smith (Case Reports in Pediatrics)
A previously healthy 11-year-old female, who emigrated from Central America four years prior, was admitted with eight days of fever, night sweats, and anorexia. Past medical history included severe bronchiolitis, varicella, and hepatitis A as a child. Upon admission, her physical exam was significant for nontender cervical lymphadenopathy, intermittent erythematous papules on the upper extremities, and mild abdominal tenderness. Initial laboratory studies revealed leukopenia, anemia, elevated inflammatory markers, and antibodies to HIV-1 in the patient’s serum and cerebrospinal fluid. Computed tomography scan was remarkable for many small nodules throughout the lungs and widespread lymphadenopathy. Additional testing confirmed the diagnosis of HIV/AIDS with a CD4 count of 52 cells/mm3, complicated by disseminated histoplasmosis. This case is significant because it represents a late presentation of vertically transmitted HIV with disseminated histoplasmosis in a nonendemic region as the AIDS-defining illness. This highlights the importance of maintaining a broad differential for opportunistic infections, especially among those who have spent a significant amount of time in a country where unusual pathogens may be more common. This case also considers the utility of antigen testing as a sensitive diagnostic test in immunocompromised patients.